Il "Commento a Isaia" di Basilio di Cesarea una replica alla recensione di M. Simonetti, "Augustininum 54 (2014), 561-567 - Cattaneo, Enrico 1943- (2015)
In a recent book (Il Commento a Isaia di Basilo di Cesarea, Roma 2014 [SEA 139]) Cattaneo argued without hesitation for the authenticity of that Basilian work (PG 30, 117-668). Prof. Manlio Simonetti in his review of this book – Augustinianum 54 (2014), 561-567 – expressed an opinion totally opposed, believing inconclusive the arguments presented by the Author. With this reply, the Author tries to answer the objections of Simonetti, and concludes by confirming his original position.